Desempenho ambiental do plano diretor de gerenciamento de resíduos sólidos da Construção Civil do Consórcio INTERPAR: interligação das unidades de gasolina e coque: Petrobras: Araucária – PR - Souza, João Luiz Martins de (2013)
The present work assessed the environmental performance of the Construction Waste Management Plan (CWMP), of the INTERPAR Consortiumfor Interconnections of Gasoline and Coke units at Repar – Araucaria, PR.This plan contained assumptions and procedures for the implementation of management activities, and its performance assessmentwas conducted with the help of a single indicator,viz. the Site Waste Indicator. The present study evaluated the plan considering all service fronts and all the steps that are part of the solid waste management: sorting, segregation and others. Thus, the work included: identification of procedures and methods adopted, assessment of field activities, and environmental performance evaluation. These activities were conducted by means of document analysis and exploratory research with a questionnaire administered to workers at different levels, and a checklist consisting of items and (or) parameters of the CWMP. The work diagnosed several problems in the stages of management, common to large construction sites. It was concluded thatthe performance was "low or unsatisfactory ", since all three indicators adopted (RTS, RAI and RAF) received a poor evaluation, i.e. activities performed at the service fronts did not meet the parameters specified by the CWMP.